Features Applications of the Approaches When Constructing Efficient Algorithms During the Modelling of Some Intracanal Flows; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 110 : Thermophysical Basis of Energy Technologies - Borisov B. V. Boris Vladimirovich (2016, 2016)
Title screen